The differential development of epistemic beliefs in psychology and computer science students: A four-wave longitudinal study. (June 2017) - Rosman, Tom; Mayer, Anne-Kathrin; Kerwer, Martin; Krampen, Günter
Abstract: This article analyses the differential development of discipline-specific epistemic beliefs (i.e., beliefs about the nature of knowledge) in computer science and psychology. With regard to computer science, a "hard" discipline, we expected absolute beliefs (knowledge as objective "truths") to increase over time. In contrast, in the more "soft" discipline of psychology, we expected absolute beliefs to be low and stable, and multiplistic beliefs (knowledge as subjective "opinions") to follow an inversely U-shaped trajectory. Hypotheses were tested in a three-semester long four-wave study with 226 undergraduates. Data were analysed by multi-group growth modelling for parallel processes. In computer science, absolute beliefs indeed increased over the study period. In psychology, an initial increase in multiplistic beliefs was followed by a steep decrease. We therefore suggest that epistemic "sophistication" should be conceived of as a flexible adaptation of epistemic judgments to the characteristics of specific contexts, and not as a generalized developmental sequence. Highlights: Epistemic belief development differs greatly between disciplines. Absolute beliefs are high and increase in computer science students. In psychology, multiplistic beliefs follow an inversely U-shaped trajectory. We suggest that learners flexibly adapt their epistemic judgments to contexts.